Prepare a variation according to the control of the movement field and its effect on learning the skill of the front hands jump and some Kinetic abilities on the mat of ground movements. - AHMED OKAB AL-HUSEEINAWI, NADIHM (International Journal of Psychosocial Rehabilitation, 2020)
Modern research includes, according to the stage that takes place in the fields of life, the most important and basic of which is the scientific field. Through the process of transferring experiences between generations, paths of development and progress that have reached the highest levels in our present time are prepared and that this occurs through the continuation of experiences and the best process of transfer of experiences is learning, that innovation Methods and methods of learning have become the concern of researchers, so we notice this through the nature of the change that takes place between generations with the change of concepts; the old methods and methods become obsolete with the factor of time, and the nature of the techniques that are used in the learning process has a limited impact to become problems determined by the observation of workers, researchers, and experts.